Intraoperative computer‐assisted prediction of intraarticular contact pressures in the knee during high tibial osteotomy. Issue 2 (3rd December 2018) - Panzica, Martin; Westphal, Ralf; Citak, Musa; Hawi, Nael; Liodakis, Emmanouil; Goesling, Thomas; Krettek, Christian; Stuebig, Timo; Suero, Eduardo M.
Abstract: Objectives: To develop an accurate intraoperative method to estimate changes in intraarticular contact pressures during high tibial osteotomy (HTO). Methods: Changes in knee alignment and pressure were monitored in real time in seven cadaver specimens that received HTO. Intraarticular contact pressure (N/mm 2 ) in each knee compartment was estimated based on extraarticularly acquired data (leg alignment, correction, and ankle tilt) and based on the application of an axial force of half bodyweight (400‐450 N). Results: Contact pressure estimation was more accurate in the lateral compartment ( R 2  = 0.940) than in the medial compartment of the knee (R 2  = 0.835). The optimism‐corrected R 2 was 0.936 for the lateral compartment and 0.821 for the medial compartment. Conclusions: We have established a framework for estimating the change in intraarticular contact pressures based on extraarticular data. This research could be helpful in generating appropriate algorithms to estimate joint alignment changes based on applied loads.